Temporal Tendinitis in Craniomandibular Dysfunction (CMD) – Does it Really Exist? A Temporomandibular MRI Investigation - Stimmer, Herbert; Grill, Florian; Waschulzik, Birgit; Nieberler, Markus; Wolff, Klaus-Dietrich; Kolk, Andreas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
Objectives The aim of the study was to analyze the role of temporal muscle and particularly tendon pathology in patients suffering from craniomandibular dysfunction (CMD) using magnetic resonance imaging.Materials and Methods Retrospective analysis of MRI examinations was carried out with regard to temporal muscle fibrosis and fatty degeneration and particularly temporal tendon rupture, thickening, and degenerative signal alterations. Descriptive statistics and the Mann-Whitney U-test were used for statistical evaluation.Results Structural lesions of temporal muscle parenchyma were the absolute exception. PD hyperintensity, pronounced contrast enhancement, or peritendinous fluid collections along the temporal tendon were found only to a small extent, and a (partial) rupture occurred in only one case. The tendon diameter showed only slight variability. The Mann-Whitney U-test provided no results indicating a causal connection between degenerative joint or disc disease and temporal tendon pathology.Conclusion A large sample of 128 magnetic resonance imaging examinations provided no evidence of a major role of temporal tendinitis in clinical CMD syndrome.Key Points: Citation Format
Keywords: temporal tendon; tendinitis; temporomandibular joint (TMJ); craniomandibular dysfunction (CMD); magnetic resonance imaging (MRI); head/neck; MR-imaging; inflammation